Virtual tour of IITA - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
Mercy, a researcher takes children on a tour of what IITA is about; and how IITA has been transforming African agriculture by ensuring food security and creating job opportunities for millions of Africans through its groundbreaking research and youth-centered entrepreneurial projects across Africa.